Syzygium jambos L. Alston: An Insight Into its Phytochemistry, Traditional Uses, and Pharmacological Properties - Ochieng, Melvin Adhiambo; Ben Bakrim, Widad; Bitchagno, Gabin Thierry M.; Mahmoud, Mona F.; Sobeh, Mansour (Frontiers in Pharmacology, 2022)
Medicinal plants have been used since ancient times for human healthcare as drugs, spices, and food additives. The progress in technology and medicine observed, the last decades, has improved the quality of life and healthcare but with worrisome drawbacks. Side effects caused by synthetic drugs for instance originate sometimes irreversible health disorders. Natural substances, in contrast, are biologically and environmentally friendly. Syzygium jambos L. (Alston) also known as rose apple conveys a long history as essential traditional medicine with a broad spectrum of application in various cultures. The plant discloses a diverse group of secondary metabolites and extracts that displayed major susceptibilities towards various health concerns, especially stress-related and inflammatory diseases. Despite a rich literature about the plant, the chemistry and biology of S. jambos have not been comprehensively reviewed yet. Accordingly, we present herein a literature survey of rose apple which aims to draw the chemical identity of the plant and establish a consistent discussion on the respective biological application of plant extracts and their corresponding traditional uses. The present work could provide a scientific basis for future studies and necessary information for further investigations of new drug discovery.